On product warnings - Hagemeyer, Caroline; Coulthard, Malcolm (Language and Law / Linguagem e Direito, 2017)
Patient information leaflet (PIL) is the offcial label for the written information that accompanies medicines and that is intended to maximize the effective use of the medicine (van der Waarde, 2004). However, studies show that this information is not simply inefficiently conveyed (Pander Maat and Lentz, 2011) but that it can even introduce health risks. This article examines the adequacy of the PILs included in a sample of over-the-counter medicines sold in the UK and in Brazil. The analysis focuses on textual characteristics of the warning sections of the PILs, in order to assess their readability and intelligibility. We also note that there are occasions when a consumer, although able to read and understand the text, may not realise the signiffcance or the importance of the warning, as it is not expressed sufficiently strongly. In examining this problem we draw on Tiersma’s (2002: 55) observation that a good warning “is one in such form that could reasonably be expected to catch the attention of a reasonably prudent [person] in the circumstances of its use and whose content is understandable”. Results are presented to show that, despite the structural differences between the Brazilian and the English PILs, both present problems due to the overuse of indirect, complex and vague language, which can lead the reader to infer information that is inaccurate, incomplete and at times just plain wrong. In addition, it will be shown that the headings of some sections are an inadequate guide to their content, particularly as far as the location of warnings is concerned. Results strongly suggest that one major purpose of PILs is to help the manufacturer to avoid litigation.